BRAINSTORMING DALAM PENCEGAHAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) OLEH IBU - Deny M. Hardita; Nuzul Qur'aniati; Kristiawati Kristiawati (Universitas Airlangga, 2014)
Introduction: Problem of Acute Respiratory Infections (ARI) is still as a major cause of morbidity and mortality in children. High incidence of ARI is influenced by several factors, such as the lack of mother’s knowledge and attitude about ARI disease. The purpose of this study was to analyze the effect of the application of brainstorming method on mother’s knowledge and attitude in prevention of ARI to toodler. Methods: This study was used pra-experimental (one-group pre-post test design). Sampling was got using proportional random sampling technique. There were 19 respondents in this study. The independent variable in this study was the application of brainstorming method, while the dependent variable in this study were knowledge and attitude. The Data was collected using a questionnaire and analyzed using Wilcoxon Signed Rank Test, with significance α = 0.05. The Wilcoxon Signed Rank Test showed that health education with brainstorming method was affected knowledge (p = 0.025) and attitude (p = 0.02) of mother.Results: The results of this study showed that health education using brainstorming method can improve knowledge and attitude of mothers in prevention of ARI to toodler.Conclussion: Health education using brainstorming method can be used as an alternatives way to prevent ARI to children. Future studies are expected to use a control group and research other factors that influence behavior.